2016
DOI: 10.1038/ncomms11390
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of human ribosomal proteins in nucleolar structure and p53-dependent nucleolar stress

Abstract: The nucleolus is a potent disease biomarker and a target in cancer therapy. Ribosome biogenesis is initiated in the nucleolus where most ribosomal (r-) proteins assemble onto precursor rRNAs. Here we systematically investigate how depletion of each of the 80 human r-proteins affects nucleolar structure, pre-rRNA processing, mature rRNA accumulation and p53 steady-state level. We developed an image-processing programme for qualitative and quantitative discrimination of normal from altered nucleolar morphology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
184
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(217 citation statements)
references
References 56 publications
15
184
2
1
Order By: Relevance
“…For side-by-side comparisons of cells from the same tissue we employed clonal expression of transgenic Rexo5 shRNA under the hsFlp-Tubulin-GAL4 driver and examined nucleolar differences of RNAi clones compared to wild-type cells in the gut at the L3 larval stage (Figure 6A–A″, S6P,Q). Rexo5 knockdowns showed a 4-fold increase of nucleolar size compared to wild-type cells, indicative of increased ribosomal nucleolar stress (Figure 6A′″) (Boulon et al, 2010; Nicolas et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…For side-by-side comparisons of cells from the same tissue we employed clonal expression of transgenic Rexo5 shRNA under the hsFlp-Tubulin-GAL4 driver and examined nucleolar differences of RNAi clones compared to wild-type cells in the gut at the L3 larval stage (Figure 6A–A″, S6P,Q). Rexo5 knockdowns showed a 4-fold increase of nucleolar size compared to wild-type cells, indicative of increased ribosomal nucleolar stress (Figure 6A′″) (Boulon et al, 2010; Nicolas et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…1). While NPM1 silencing was not sufficient to perturb cell viability (Grisendi et al, 2005;Maggi et al, 2008) or rRNA processing (Maggi et al, 2008) in various cell lines that express WT U2AF1, NPM1 silencing has been shown to alter nucleolar shape (Nicolas et al, 2016) and the localization of ribosome biogenesis factors to the nucleolus (Castle et al, 2012). We propose increased cellular dependence on NPM1 under conditions of elevated mRNA translation such as in the presence of U2AF1-S34F.…”
Section: Discussionmentioning
confidence: 71%
“…They together with 5S rRNA (5S ribonucleoprotein particle, 5S RNP, rRNA in complex with proteins) inhibit Mdm2 activity and maintain the structural integrity of nucleoli (Nicolas et al 2016). 5S RNP–Mdm2–p53 pathway may be activated upon impairment of ribosome production, including downregulated RPS19 synthesis.…”
Section: A Nucleolus As An Opponent Of Cancer Cells Via P53-dependentmentioning
confidence: 99%